An unusual case of lateral vaginal wall leiomyoma: case report - Kabra, Shashi L.; Singh, Renu; Madaan, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Twenty to thirty percent of women in the reproductive age group are affected with leiomyomas, the most frequent benign tumor of the uterus. Only 300 occurrences of vaginal leiomyomas have been documented, hence they are still a rare condition. Because of their low incidence and wide range of nonspecific clinical symptoms, tumors are assumed to originate from Mullerian smooth muscle cells in the sub-epithelium of the vagina. However, these cells can easily be misdiagnosed. Usually located in the anterior vaginal wall are vaginal leiomyomas. Here, we describe a case of left upper lateral vaginal wall leiomyoma in a 40-year-old multigravida. She presented with pelvic fullness. Cervical fibroid was diagnosed based on physical examination and MRI. Under anesthesia, the tumor was removed vaginally, and histology revealed a vaginal leiomyoma. Vaginal leiomyomas are uncommon tumors; however, they can present with a range of clinical symptoms and be mistakenly classified as cervical fibroid before surgery. The most effective therapy approach seems to be vaginal tumor excision followed by a histological investigation. To raise awareness of the disease and lower the possibility of a misdiagnosis and improper treatment, the current instance was disclosed.